The Suitable Sites for Seagrass Transplantation in Lae-Lae Island and Sandbar According to Sediment Characteristics - Lanuru, Mahatma; Patandianan, Priska Bungaran; Wahidin, Caesar Islami; Permatasari, Permatasari (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
The success of a seagrass transplantation effort depends on identifying locations with optimal sediment characteristics for seagrass growth and survival. This study analyzed sediment characteristics of seagrass bed sediment and adjacent unvegetated sediment on Lae-Lae Island and Lae-Lae sandbar (Makassar, South Sulawesi) to determine the suitable sites for seagrass transplantation. Seagrass bed sediments and adjacent unvegetated sediments were collected from four locations to measure sediment particle size, redox potential, organic matter, water content, nitrate, and phosphate concentrations. Analysis of similarities (ANOSIM) was performed using PAST (Paleontological Statistics) software to determine a suitable site for seagrass planting (transplantation). The results show that surface sediments in the Lae-Lae island are composed of medium sand and coarse sand with grain sizes varying from 0.290 to 0.768 mm, whereas in the Lae-Lae sandbar, the sediment is composed of medium sands (0.371 – 0.460 mm). Redox potential (Eh) varied from -34.1 to -65.7mV, water contents were 1.3 to 1.8%, organic contents were 19.85 to 38.53%, nitrate content varied from 0.60 to 3.47, and phosphate content varied from 7.42 to 14.19 ppm. The percentage of mud (clay and silt) and organic matter were slightly higher in seagrass bed sediments compared to unvegetated area sediments. No differences in nutrient contents (nitrate and phosphate) between seagrass sediments and unvegetated were observed in this study. ANOSIM results show no difference in the sediment characteristics between a seagrass bed and unvegetated sand at the north and south sides of Lae-Lae Island and Lae-Lae sandbar, which means that these three sites are suitable for seagrass transplantation.Keywords: sediment, seagrass, transplantation, site selection, ANOSIM, Lae-Lae